SIMPLE LAWSUIT IN SHARIA ECONOMIC DISPUTES. A CASE STUDY OF DECISION NUMBER 1/PDT.G.S/2019/PA.KDS - Nurhisam, Luqman; Eriyanti, Nahara (Universitas Islam Negeri Ar-Raniry, 2024)
As the activities of the Sharia economy develop, the number of Sharia economic dispute cases submitted to the Religious Court has increased. One of the cases decided by the Kudus Religious Court is the Breach of Contract Lawsuit with Decision Number 1/P.dt.G.S/2019/PA.Kds. The Supreme Court issued Regulation Number 14 of 2016 concerning Procedures for the Settlement of Sharia Economic Disputes, which includes simple lawsuits and ordinary lawsuits. Simple lawsuits are further regulated in Supreme Court Regulation Number 2 of 2015, which was later amended to Supreme Court Regulation Number 4 of 2019 concerning Procedures for the Settlement of Simple Lawsuits. This regulation aims to ensure that the resolution of Sharia economic disputes is simpler, faster, and less costly. This research aims to analyze the process and mechanism for resolving simple Sharia economic dispute lawsuits at the Kudus Religious Court, examine the judges' considerations in deciding Sharia economic dispute cases, and identify challenges in resolving Sharia economic disputes. The type of research used is field research with a qualitative approach, utilizing primary, secondary, and tertiary data. The results of the study show that the process and considerations of the judges in Decision Number 1/P.dt.G.S/2019/PA.Kds are in accordance with applicable regulations. However, the resolution of the case takes quite a long time. Therefore, judges in the Religious Courts are required to have competence in Sharia economic law to handle cases more effectively and efficiently.